Cross-disciplinary variation in metadiscourse: A corpus-based analysis of Russian-authored research article abstracts - Olga A. Boginskaya (Training, Language and Culture, 2022)
The article deals with metadiscourse variation in academic texts across disciplinary boundaries. Its main focus is on the distribution of metadiscourse markers in Russian-authored academic prose in the field of applied linguistics and engineering. The study assumes that the distribution of metadiscourse devices is determined by disciplinary norms. The theoretical basis of the study is Hyland’s taxonomy of metadiscourse markers. With the aim of investigating metadiscourse in English-medium research article (RA) abstracts by Russian authors, the present study adopted a combination of quantitative and qualitative methods. The results revealed that RA abstracts feature four types of metadiscourse markers whose distribution varies across two disciplines representing the humanities and hard sciences. The study also investigated the degree of familiarity of linguistics and engineering scholars from leading Russian universities with metadiscourse devices and their awareness of the need to use them in research articles. To achieve this goal, a survey was conducted to obtain data on knowledge of metadiscourse as a discursive strategy. The findings carry therefore pedagogical implications for academic writing course designers and instructors and can enhance non-native English writers’ knowledge of academic writing conventions in the discipline.